Trinuclear heterobimetallic Ni2Ln complexes [L 2Ni2Ln][ClO4] (Ln = La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, and Er; LH3 = (S)P[N(Me)N=CH-C6H 3-2-OH-3-OMe]3): From simple paramagnetic complexes to single-molecule magnet behavior - Chandrasekhar, V. (2014)
10.1021/ic800199x